1- y2 - 2yz - z2 factories
Answers
Answered by
5
Step-by-step explanation:
1- y2 - 2yz - z2
= 1-(y2 + 2yz + z2)
= 1- (y+z)^2
= (1)^2-(y+z)^2
= (1+y+z)(1-y-z)
Answered by
6
Answer:
thanks thanks thanks thanks thanks thanks thanks thanks thanks thanks thanks
Attachments:
![](https://hi-static.z-dn.net/files/d5d/27353b41016a1d10fd7769f3134c1786.jpg)
Similar questions
Environmental Sciences,
3 months ago
Physics,
3 months ago
Political Science,
7 months ago
Math,
7 months ago
English,
1 year ago
CBSE BOARD X,
1 year ago
Math,
1 year ago